2018
DOI: 10.2147/cmar.s174950
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary therapy for scirrhous gastric cancer: a retrospective analysis and proposal of new treatment strategy

Abstract: BackgroundScirrhous gastric cancer (SGC) is highly invasive and metastatic because of its interactions with stromal cells, such as fibroblasts and macrophages, and extracellular matrix, leading to a higher incidence of peritoneal metastasis (PM) than other gastric cancers (GCs). Taxane-based intraperitoneal chemotherapy (IPC) is a promising therapy for PM. We retrospectively analyzed outcomes of multidisciplinary therapies that included IPC for SGC.Patients and therapyOf 1,679 GC patients treated between 1990 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Intraperitoneal chemotherapy is also being investigated as an alternative to conventional IV chemotherapy for peritoneal carcinomatosis. Taxanebased IPC takes advantage of the antifibrotic properties of the agent [1]. Adipocytes found around tumors, along their borders, or within the tumor itself, serve a function similar to CAFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraperitoneal chemotherapy is also being investigated as an alternative to conventional IV chemotherapy for peritoneal carcinomatosis. Taxanebased IPC takes advantage of the antifibrotic properties of the agent [1]. Adipocytes found around tumors, along their borders, or within the tumor itself, serve a function similar to CAFs.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer (GC) ranks as the fifth most common malignancy worldwide, with approximately 1.1 million new cases annually. It stands out as having one of the highest mortality rates with the third most deaths [1][2][3][4]. Linitis Plastica (LP), a subtype of gastric cancer, constitutes 10% of all GC cases [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“… 17 Patients received the chemotherapy of physician's choice including taxane‐based intraperitoneal chemotherapy. 4 Immune checkpoint inhibitor was not used in all cases. Among the patients who were judged as resectable, gastrectomy was performed 4 to 8 weeks after their last day of chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, molecular mechanisms of peritoneal metastasis are poorly understood. Although various treatments have been developed for peritoneal metastasis, including systemic chemotherapy, intraperitoneal chemotherapy, sufficiently satisfactory outcomes have yet to be achieved 3 , 4 , 5 ; this indicates the need for novel treatment strategies, in addition to conventional surgery and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the neoadjuvant chemotherapy for patients with SGC (JCOG0501) could not find a survival benefit (4). One of the reasons for the poor prognosis of SGC is the lack of effective therapeutic agents based on the characteristic molecular biology of SGC (5,6). Then, in this study, we aimed to find the characteristic features and useful therapeutic targets for SGC.…”
Section: Introductionmentioning
confidence: 98%